2021
DOI: 10.3389/fimmu.2021.696268
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Acquired Disseminated BCG in the Context of a Delayed Immune Reconstitution After Hematological Malignancy

Abstract: ContextDisseminated infections due to Mycobacterium bovis Bacillus Calmette-Guérin (BCG) are unusual and occur mostly in patients with inborn error of immunity (IEI) or acquired immunodeficiency. However, cases of secondary BCGosis due to intravesical BCG instillation have been described. Herein, we present a case of severe BCGosis occurring in an unusual situation.Case DescriptionWe report one case of severe disseminated BCG disease occurring after hematological malignancy in a 48-year-old man without BCG ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In countries where BCG is routinely administered in infancy, disseminated Mycobacterium bovis-BCG infection is commonly seen in children with underlying inborn error of immunity (IEI) like severe combined immunodeficiency (SCID) and chronic granulomatous disease [5]. Wang and colleagues evaluated 22 cases of disseminated BCG disease in China for immunodeficiency, and found that at least 16 of them (72.7%) suffered from definite immunodeficiency simultaneously [6].…”
Section: Discussionmentioning
confidence: 99%
“…In countries where BCG is routinely administered in infancy, disseminated Mycobacterium bovis-BCG infection is commonly seen in children with underlying inborn error of immunity (IEI) like severe combined immunodeficiency (SCID) and chronic granulomatous disease [5]. Wang and colleagues evaluated 22 cases of disseminated BCG disease in China for immunodeficiency, and found that at least 16 of them (72.7%) suffered from definite immunodeficiency simultaneously [6].…”
Section: Discussionmentioning
confidence: 99%
“…While it's mechanisms of action are not completely understood, it is thought to initiate inflammation and cellular immune activity resulting in an anti-tumor response [6]. Moreover, being a live Mycobacterium, the possibility of it escaping the bladder after intravesical instillation causing a systemic infection ("BCGemia") has been well described [7,8]. Thus, there is understandable concern that in patients who are immunologically compromised, either iatrogenically and/or because of underlying diseases, intravesical instillations of BCG will not be effective and potentially can be unsafe.…”
mentioning
confidence: 99%
“…Thus, there is understandable concern that in patients who are immunologically compromised, either iatrogenically and/or because of underlying diseases, intravesical instillations of BCG will not be effective and potentially can be unsafe. While several small, single-institution historical series confirm its safety and efficacy in treating bladder cancer patients who are immunocompromised [7,[9][10][11][12][13][14][15][16], no large-scale assessment has been made, and in large prospective randomized studies testing BCG's efficacy, immunosuppressed patients and/or those receiving corticosteroids chronically have intentionally been excluded from participation (e.g., SWOG S1602 [PRIME]).…”
mentioning
confidence: 99%